Pengaruh harga dan kualitas layanan terhadap kepuasan konsumen di poljam mart - Putri Indika (LP2M Politeknik Jambi, 2026)
This study aims to analyze the partial and simultaneous influence of price and service quality on customer satisfaction at Poljam Mart. Increasing competition in the minimarket business requires Poljam Mart to implement competitive pricing strategies and excellent service quality to retain customers. The research method used is a quantitative approach, with questionnaires distributed to 93 respondents consisting of residents of Permata Land Housing and the academic community of Jambi Polytechnic, selected using a purposive sampling technique. Data were analyzed using multiple linear regression assisted by the SPSS program. The results showed that the price variable (X1) has a positive and significant effect on customer satisfaction (Y) with a significance value of 0.001 < 0.05 and a t-count of 2.355 > 1.987. The service quality variable (X2) also has a positive and significant effect on customer satisfaction with a significance value of 0.001 < 0.05 and a t-count of 4.145 > 1.987. Simultaneously, price and service quality influence customer satisfaction with a coefficient of determination (R Square) of 0.248, indicating that these two variables contribute 24.8% to customer satisfaction at Poljam Mart.